Prospective Exploratory Study of the Clinical Significance of Circulating Tumor Cells in Patients With Small Cell Lung Cancer Exposed to Prophylactic Cranial Irradiation - Deng, Lei; Zhang, Ye; Zhang, Wen; Feng, Lin; Zhang, Kaitai; Wang, Wenqing; Zhou, Zongmei; Wang, Luhua; Hui, Zhouguang (Frontiers in Oncology, 2021)
Objective: Circulating tumor cells (CTCs) can predict the efficacy of anti-cancer treatments and indicate prognosis. Here we investigate the significance of CTCs in relation to the prediction of treatment efficacy and prognosis in patients with small cell lung cancer (SCLC) who have received prophylactic cranial irradiation (PCI). Methods: CTCs were detected in 20 patients with SCLC before and after PCI using the oHSV1-hTERT-GFP method. The primary endpoints were progression-free survival (PFS) and overall survival (OS). Results: Eleven patients had limited-stage SCLC, and nine had extensive-stage SCLC. All patients completed chemo-radiotherapy and received PCI. The median baseline CTC count before PCI was 12. After PCI, the median CTC count was 4. The median follow-up time for all enrolled patients was 39.2 months. The median PFS and OS were significantly reduced in patients with ≥4 CTCs after PCI compared to those with <4 CTCs (PFS, 28.1 months vs. not reached, p = 0.001; OS, not reached vs. not reached, p = 0.029). Seven of the 10 patients with ≥4 CTCs after PCI failed after treatment, whereas the10 patients with <4 CTCs after PCI remained alive without tumors. The median PFS and OS were significantly improved in patients who exhibited a rate of CTC decline of ≥58% after PCI compared with patients who exhibited a decline rate of <58% (PFS, 26.4 months vs. not reached, p = 0.006; OS, not reached vs. not reached, p = 0.029). Conclusion: In SCLC patients who receive PCI, the CTC count and rate of CTC decline after PCI significantly correlate with prognosis.